Neurological conditions among pediatric patients seeking care at a tertiary level hospital in western Kenya - Eren Oyungu; Megan Song McHenry; Chrispine Oduor; Jamil Said; O’Brien Kyololo; Jane R. von Gaudecker (PLoS ONE, 2025)
Neurological disorders significantly contribute to the global burden of diseases, especially in sub-Saharan Africa. However, within local contexts in Kenya, little is known about the pattern of neurological and neurosurgical disorders within pediatric populations. A 3-month cross-sectional observational study was conducted at a tertiary-level hospital in western Kenya to describe these patterns and basic characteristics of the patient population. Consecutive pediatric patients presenting for neurological and neurosurgical care in inpatient and outpatient settings at Moi Teaching and Referral Hospital were included in the study. A total of 485 patients were included in the study. The average age of the patients was 6.2 years, and most were male (57%). Out of these, 30.3% (n=147) were inpatients, and 69.7% (n=338) were outpatients. Inpatients traveled longer distances compared to outpatients (P<0.001), and most were from rural areas (P<0.0001), while outpatients were mostly from peri-urban areas (P<0.0001). The majority of the inpatients (25%) and outpatients (69%) had a diagnosis of epilepsy. Other common neurological conditions were neurodevelopmental delays and meningitis/encephalitis. Given the burden of these diseases, there is a need to improve the health infrastructure for better access to quality healthcare. Specifically, improving epilepsy care, supporting neurodevelopmental programs, managing infectious diseases, and expanding neurosurgical services can enhance health infrastructure for this population.